SELF-PERCEIVED HEALTH STATUS AND NUMBER OF SICK DAYS PEOPLE WITH ASTHMA AND CHRONIC OBSTRUCTIVE PULMONARY DISEASE - Milić, Marija J; Stevanovic, Jasmina; Bjelovic, Milos; Parlic, Milan; Gazibara, Tatjana (HEALTH CARE, 2022)
Background/aim: There is a lack of studies focusing on the comparison of health-related quality of life (HRQOL) between people with asthma and people with chronic obstructive pulmonary disease (COPD). The purpose of this study was to examine and compare self-reported health status in people who have asthma and people who have COPD. Methods: Data were collected from adult participants who came to primary health care institutions using a general questionnaire to examine their health status and the Serbian version of the HRQOL-14. The propensity score method was used to match people with asthma and COPD on age, gender, education level and adherence to therapy. Results: A total of 1,954 patients (47% men, 53% women) were included in the study. The average age of patients with asthma was 49.4±15.5, whereas the patients with COPD were older - 59.5±12.4. In both groups, 60% of the participants reported their health status as poor. No difference was found between patients with asthma and patients with COPD in terms of self-perceived general health status and the number of sick days. Patients with asthma and COPD reported the greatest number of days with sleep disorders, followed by days with symptoms of anxiety and depressive symptoms and the least number of days with having pain. Conclusion: These data indicate the need to improve sleep patterns in people with asthma and COPD. These data could be used to further examine specific features of sleep among people with asthma and COPD.